QUALITY OF PRESCRIPTIONS IN PRIMARY CARE: WE NEED TO TARGET THAT - NAYARA CRISRINA RABELO BANDEIRA; FRANCISCO CLÉCIO DA SILVA DUTRA; PATRÍCIA FREIRE DE VASCONCELOS; VANESSA EMILLE CARVALHO DE SOUSA FREIRE; RHANNA EMANUELA FONTENELE LIMA DE CARVALHO; JEFERSON FALCÃO DO AMARAL (Sociedade Brasileira de Enfermagem em Feridas e Estética, 2021)
Aim: To identify errors in drug prescriptions and its causes in a primary healthcare center. Method: Cross-sectional study carried out in a primary healthcare center in northeastern Brazil. A total of 707 drug prescriptions were analyzed using an instrument with pre-established criteria, according to the country's legal provisions regarding drug prescription. An Ishikawa diagram was created to identify the possible causes for the identified errors. Results: A total of 138 drug prescriptions (19.5%) presented information failure or inadequacy. From the errors found, 116 (16.41%) were related to information on dosage. The Ishikawa diagram showed opportunity for improvement in management, training, and technical/professional qualification. Conclusion: The errors seen on drug prescriptions at a primary healthcare center were related to illegibility, absence of dosage, and absence of mandatory patient information. Organizational, technical, scientific, and political factors were identified as the roots of the identified errors.